2021
DOI: 10.21470/1678-9741-2020-0653
|View full text |Cite
|
Sign up to set email alerts
|

Total Arterial Coronary Bypass Graft Surgery is Associated with Better Long-Term Survival in Patients with Multivessel Coronary Artery Disease: a Systematic Review with Meta-Analysis

Abstract: Introduction The benefit of total arterial revascularization (TAR) in coronary artery bypass grafting (CABG) remains a controversial issue. This study sought to evaluate whether there is any difference on the long-term results of TAR and non-TAR CABG patients. Methods The Medical Literature Analysis and Retrieval System Online (MEDLINE), Excerpta Medica dataBASE (EMBASE), Cochrane Central Register of Controlled Trials (CENTRAL/CCTR), Clinical Trials.gov, Scientific Elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 18 publications
(10 reference statements)
2
14
0
1
Order By: Relevance
“…Three recent meta-analysis have been published in this topic. 4 , 5 , 24 In a recent meta-analysis that pooled 12 small matched/adjusted observational studies of 33597 patients, TAG was associated with reduced all-cause mortality compared with conventional CABG (HR 0.85, 95% CI, 0.81-0.89). 4 Other authors, including different studies, concluded that TAG with BIMA may offer a higher protective long-term survival effect at the expense of a higher risk of DSWI (relative risk 1.44, 95% CI 1.17-1.77).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three recent meta-analysis have been published in this topic. 4 , 5 , 24 In a recent meta-analysis that pooled 12 small matched/adjusted observational studies of 33597 patients, TAG was associated with reduced all-cause mortality compared with conventional CABG (HR 0.85, 95% CI, 0.81-0.89). 4 Other authors, including different studies, concluded that TAG with BIMA may offer a higher protective long-term survival effect at the expense of a higher risk of DSWI (relative risk 1.44, 95% CI 1.17-1.77).…”
Section: Discussionmentioning
confidence: 99%
“… 4 Other authors, including different studies, concluded that TAG with BIMA may offer a higher protective long-term survival effect at the expense of a higher risk of DSWI (relative risk 1.44, 95% CI 1.17-1.77). 5 The most recent papers summarizing outcomes of 14 studies and 22746 patients (8941 TAG and 13805 non-TAG) showed that the pooled hazard ratio for long-term mortality (>10 years) was lower in TAG (HR 0.68; 95 %CI 0.59-0.78, P<0.001), 24 but prospectively hi-quality evidences are still awaited to confirm those findings. An ongoing trial with a target sample size of 4300 patients comparing multiple arterial graft with single arterial graft, the Randomization of Single vs Multiple Arterial Grafts (ROMA) trial (NCT03217006) will hopefully provide a definitive answer as to whether using more arterial grafts will lead to better survival and lower number of adverse events in the long term.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…where A is the cross-sectional area of the vessel in cm 2 , Q is the flow rate in cm 3 /s, P is the pressure in dyne/cm 2 , x is the axial dimension along the vessel in cm, ρ is the density of blood assumed essentially incompressible with a constant value ρ ≈ 1.06 g/cm 3 , ν is the kinematic viscosity (ν = µ ρ ), µ is dynamic viscosity with µ = 0.046 dyn•s/cm 2 (32, 33) and α is the momentum correction coefficient (Coriolis coefficient) that accounts for the non-linear integration of cross-sectional radial velocities and determines the shape of the velocity profile, φ (r), through Equation (3), R is the lumen radius and r is the radial coordinate (34):…”
Section: Governing 1d Navier-stokes Equationsmentioning
confidence: 99%
“…internal mammary arteries (BIMA) and radial arteries (RA), on account of their longevity (3,4). However, there still exists significant variability in grafting strategy among cardiac surgeons and there remains controversy as to the optimal grafting configuration for a given patient (5).…”
mentioning
confidence: 99%